Pengaruh Keterlibatan Kerja Dan Pengalaman Kerja Terhadap Komitmen Organisasi Pegawai Di Dinas Pendidikan Kabupaten Bekasi - Andri Cahyo Purnomo; Po. Abas Sunarya; Rise Wijoyo Jati (UNIVERSITAS RAHARJA, 2018)
Organizational commitment is a person's attachment to the organization. Employees who are committed to the organization will have a strong desire to become members of the organization, the desire to strive according to the wishes of the organization, and have the trust and acceptance of the values and goals of the organization. Organizations will be more effective if their employees have a high commitment. This study aims to determine the effect of (1) job involvement, (2) work experience, (3) organizational commitment in the Bekasi District Education Office. In data analysis, this study uses causal survey method using Path Analysis Technique. This study used a sample of 97 employees in the Bekasi District Education Office who were selected using the Slovin formula. The results reveal that: first, work involvement has a direct positive effect on organizational commitment. This means that the increase in work involvement has resulted in an increase in the commitment of employee organizations at the Secretariat of the Human Resources Development Agency of the Ministry of Transportation of the Republic of Indonesia. Second, work experience has a direct positive effect on organizational commitment. This means that an increase in work experience has resulted in an increase in the commitment of employee organizations at the Secretariat of the Human Resources Development Agency of the Ministry of Transportation of the Republic of Indonesia. Third, work involvement has a direct positive effect on work experience. This means that the increase in work involvement has resulted in an increase in work experience for employees at the Ministry of Transportation's Human Resources Development Agency Secretariat. From the results of the study also found that the most influential variables are work involvement on organizational commitment, this can be proven from the results of statistical calculations with a value of r13 = 0.426, p32 = 0.328 the highest compared to the influence of other variables. Follow-up of this study, employees are expected to have high work involvement and attitude of love for their work so that employees will be more sincere and sincere in doing their work. In addition, employees will also have a great sense of responsibility and a sense of ownership of the organization and the whole that will bring the desire of employees to do work beyond what is expected, to do work optimally and maximize themselves to be more useful for the organization.